Determination of Radioactivity Levels and Excess Lifetime Cancer Risk in Soil Samples at the Environment at Al-Mishal, Libya, using Gamma-ray Spectrometry - Asma M. Othman; Areej I. Hazawi; Rasha Y. Elfallah; Mabrouka A. Abd-Ahamid (Libyan Journal of Science &Technology, 2026)
Eight soil samples collected from Al-Meshal, Libya, have been investigated. Concentrations of radionuclides in the samples were determined by a gamma-ray spectrometer using a NaI(Tl) detector with a specially designed shield. The contents of 238U and 232Th are high in the samples, and the content of 40K is higher than the permissible level. The absorbed dose rate ranged from 99.91 to 160.92nGy/h. External and internal hazard indices were also determined. The Excess Lifetime Cancer Risk (ELCR) values for all samples were found to be much higher than the permissible level of 0.29